Analgesic and Anti inflammatory Properties of Salix alba Linn and Calotropis procera Aiton Dryand - Rajendra Gyawali, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Analgesic and Anti inflammatory Properties of Salix alba Linn and Calotropis procera Aiton Dryand